2019
DOI: 10.1021/acs.orglett.9b03216
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Leptazolines A–D, Polar Oxazolines from the Cyanobacterium Leptolyngbya sp., Reveals a Glitch with the “Willoughby–Hoye” Scripts for Calculating NMR Chemical Shifts

Abstract: The bioactivity-guided examination of a Leptolyngbya sp. led to the isolation of leptazolines A–D (1–4), from the culture media, along with two degradation products (5 and 6). Density functional theory nuclear magnetic resonance calculations established the relative configurations of 1 and 2 and revealed that the calculated shifts depended on the operating system when using the “Willoughby–Hoye” Python scripts to streamline the processing of the output files, a previously unrecognized flaw that could lead to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 22 publications
1
34
1
Order By: Relevance
“…Constituent models may be run on different infrastructure than was originally intended, especially as issues around computational reproducibility are addressed ( Barba, 2019 ; Hutton et al, 2016 ). Identical code run under different computational environments may produce different results (see for example Bhandari Neupane et al, 2019 ). Such infrastructure may differ in physical or virtual architecture (e.g., laptop, supercomputer, or operating systems) or method of generating/interpreting code (e.g., different languages, compilers, package versions).…”
Section: Scale Issues To Considermentioning
confidence: 99%
“…Constituent models may be run on different infrastructure than was originally intended, especially as issues around computational reproducibility are addressed ( Barba, 2019 ; Hutton et al, 2016 ). Identical code run under different computational environments may produce different results (see for example Bhandari Neupane et al, 2019 ). Such infrastructure may differ in physical or virtual architecture (e.g., laptop, supercomputer, or operating systems) or method of generating/interpreting code (e.g., different languages, compilers, package versions).…”
Section: Scale Issues To Considermentioning
confidence: 99%
“…A series of polar oxazolines, named leptazolines A–D ( 52–55 ), were isolated from the culture media of a Leptolyngbya sp. ( Figure 16 ) [ 51 ]. Their planar structures were characterized by MS and NMR along with formation of acetate derivatives.…”
Section: Chemical Diversity Of the Secondary Metabolites Isolated mentioning
confidence: 99%
“…Interestingly, the calculations were found to vary as a function of the computer operating system (Ubuntu 16, Windows 10, MAC Mavericks, MAC Mojave). Biological assay showed that leptazoline B ( 53 ) modestly inhibited the growth of PANC-1 cells, with a GI 50 of 10 µM [ 51 ], whereas leptazoline A ( 52 ) with its aromatic chlorine atom did not show any significant activity to this cell line.…”
Section: Chemical Diversity Of the Secondary Metabolites Isolated mentioning
confidence: 99%
“…Bugs can be caused by typos, code behaving in unexpected ways, or logical flaws in the construction of the code. Outside of epidemiology, bugs have been found in code that had been used by many researchers [6] and may lead to retractions [7]. Bugs have also been found in highly influential work; a paper that informed austerity policies globally was found to have a fatal computational mistake [8].…”
Section: Introductionmentioning
confidence: 99%